Peran Guru BK dalam Mengatasi Bullying (Studi Kasus Siswa SMPN 1 Singojuruh) - Mursidi, Agus; Noviandari, Harwanti; Denada, Tasya (JURNAL KONSELING GUSJIGANG, 2024)
Bullying is an emotional problem caused by an imbalance of power between the bully and the victim, where the perpetrator continuously humiliates the victim. The purpose of this study was to find out the role of the counseling teacher in overcoming bullying at SMPN 1 Singojuruh, to find out what factors influence the occurrence of bullying at SMPN 1 Singojuruh and to find out the steps taken by the counseling teacher to deal with bullying at SMPN 1 Singojurih. The method used in this research is a qualitative case study with the subject of research counseling teachers and principals of SMPN 1 Singojuruh. The results of the study show that counseling teachers have a very important role in overcoming bullying in schools by implementing appropriate counseling strategies.